TI_GERICHTE 52.2004.201 vom 23. November 2004 , acquisto di fondi agricoli di esigua estensione giusta l'art. 2 cpv. 3 LDFR - TI Tribunale d'appello (2004)
acquisto di fondi agricoli di esigua estensione giusta l'art. 2 cpv. 3 LDFR